2017
DOI: 10.1177/2333721417703736
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Burden Experienced by Caregivers of Older Adults Who Use a Powered Wheelchair: A Cross-Sectional Study

Abstract: Objective: In this study, we aimed to describe the burden of family caregivers providing powered wheelchair-related and overall assistance and test the hypotheses that caregiver burden correlates with participation, wheelchair skills capacity, anxiety, depression, and social support. Methods: Cross-sectional study. Participants included 35 family caregivers of powered wheelchair users. Caregivers were assessed using the Power Mobility Caregiver Assistive Technology Outcome Measure, Late Life Disability Instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
(58 reference statements)
1
16
0
Order By: Relevance
“…A recent study showed patients’ wheelchair usage increases the psychological burden for the caregivers. 29 Also, we showed a non-significant positive correlation between the caregivers’ age and caregivers’ stress which was also reported in a recent study. 30 …”
Section: Discussionsupporting
confidence: 82%
“…A recent study showed patients’ wheelchair usage increases the psychological burden for the caregivers. 29 Also, we showed a non-significant positive correlation between the caregivers’ age and caregivers’ stress which was also reported in a recent study. 30 …”
Section: Discussionsupporting
confidence: 82%
“…To date, 53 instruments have been mentioned and used to provide an AT outcome measure assessment ( Multimedia Appendix 2 [ 20 - 66 ]). In addition, 3 ad hoc questionnaires and an ad hoc interview were used.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to assessing capacity (as in Wheelchair Skills Test; WST), the WST-Q assesses confidence and performance (what wheelchair users do and how they do it). In the reviewed articles, it was administered to patients and their informal caregivers [ 20 , 21 ]. With regard to patients, the studies showed that it is an effective way to evaluate variation in 32 power mobility skills (eg, the capability of putting on brakes, propelling a straight distance, and performing a reaching task from their wheelchair) in all power mobility AP users [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interpersonal Support Evaluation List-12 was used to measure 3 aspects of social support including appraisal, belonging and tangible [27]. Interpersonal Support Evaluation List-12 originated from the Interpersonal Support Evaluation List developed by Sheldon Cohen in 1985 [49] and has been used repeatedly adopted in previous studies [50][51][52][53]. For each of the 3 included aspects, there were 4 related questions in the questionnaire.…”
Section: Part 1 -Dependent Variable -Presenteeismmentioning
confidence: 99%